Voter’s Perception of Political Messages Against the Elite Classes in Spain: A Quasi‐Experimental Design - Gonzálvez-Vallés, Juan Enrique; Barquero-Cabrero, José Daniel; Enseñat-Bibiloni, Natalia (Politics and governance, 2023)
Demonization constitutes the construction of a simplified symbolic reality through the prism of hatred. The elite classes have been framed within the discourse of far-left parties in Spain to make them antagonistic to their target audience. In this area, research tends to use explicit measures, but few have used implicit measures. This article aims to assess both types of voter perceptions of anti-elite class messages in Spain. Eighty Spanish voters belonging to left- and right-wing ideologies participated in this study. Implicit attitudes were measured through the implicit association test. The result shows that demonization is deepening in various layers of society in order to provoke a confrontation with the elite classes. Social networks have emerged as a means of social control, but they are not perceived as such by the subjects but rather as an additional informational or purely propagandistic element. But even among the public who are aware of the latter, the more their perception of the elite classes is limited to demonization, the more extreme their social vision is.